Evaluation of MicroScan Rapid Pos Combo panels for identification of staphylococci. - Stoakes, L (1992)
MicroScan Rapid Pos Combo panels (Baxter Diagnostics, Inc., MicroScan, West Sacramento, Calif.) contain substrates conjugated with fluorophores and substrates with a fluorescent pH indicator. AutoSCAn W/A, an automated panel processor equipped with a fluorometer, reads the panels after 2 h of incubation and can identify staphylococci to the species level. We tested 239 strains belonging to 17 species of staphylococci. All the strains were identified by conventional methods (W.E. Kloos and K.H. Schleifer, J. Clin. Microbiol. 1:82-88, 1975) and by the MicroScan Rapid ID system. The system correctly identified 219 (91.6%) strains; nine (3.8%) identification results were probably correct, and six (2.5%) results were incorrect. The system designated five (2.1%) strains as rare biotypes. The automated MicroScan Rapid ID system is useful and reliable in identifying most human isolates of staphylococci encountered in the clinical laboratory.